Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal element, polymer and compound

By introducing a specific partial structure into the polymer, the liquid crystal aligning agent achieves improved solubility, storage stability, and high voltage retention, addressing issues of low transmittance and durability in liquid crystal elements, particularly in smartphone and vehicle-mounted displays.

JP7619178B2Active Publication Date: 2025-01-22JSR CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021099685
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-15
Publication Date
2025-01-22
Estimated Expiration
2041-06-15

AI Technical Summary

Technical Problem

Monomers with a benzimidazole skeleton and polymers derived from them exhibit low solubility and storage stability, leading to concerns about the stability of liquid crystal aligning agents, and the resulting films have low transmittance, affecting display quality. Additionally, liquid crystal elements require high voltage retention rates over time and robustness against external forces, especially in applications like smartphones and vehicle-mounted displays.

Method used

Incorporating a specific partial structure into a polymer, such as those represented by formulas (1-1) and (1-2), to form a liquid crystal aligning agent that undergoes thermal cyclization, forming a benzimidazole ring structure, enhancing solubility, storage stability, and maintaining high voltage holding rates while providing excellent touch panel resistance.

Benefits of technology

The solution results in a liquid crystal aligning agent that forms films with high transmittance, maintains voltage holding capability over time, and offers superior touch panel durability, ensuring reliable display performance even under external stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619178000001
    Figure 0007619178000001
  • Figure 0007619178000002
    Figure 0007619178000002
  • Figure 0007619178000003
    Figure 0007619178000003
Patent Text Reader

Abstract

To provide a liquid crystal alignment agent capable of forming a liquid crystal alignment film having high transmittance and capable of producing a liquid crystal element that shows a little decrease in voltage holding ratio even when used for a long time and has excellent touch panel resistance, and features high storage stability.SOLUTION: A liquid crystal alignment agent contains a polymer [P] having a partial structure (A) which is at least one selected from the group consisting of a partial structure represented by the formula (1-1) and a partial structure represented by the formula (1-2), where R1 and R4 each denote a monovalent thermally detachable group, R2, R3, R5 and R6 each denote a hydrogen atom or a monovalent organic group, X1 denotes a single bond, -O-, -S-, -CO-, *1-CO-O-, *1-O-CO-, -NR9-, *1-NR9-CO-, *1-CO-NR9- or the like, and A1 denotes a C1-10 alkanediyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal alignment film, a liquid crystal element, a polymer and a compound. [Background technology]

[0002] Liquid crystal elements are used in a wide range of applications, from relatively large display devices such as liquid crystal televisions and information displays to small display devices such as smartphones. The performance of a liquid crystal element is determined by various characteristics such as the alignment of liquid crystals, the magnitude of the pretilt angle, and the voltage holding ratio. In order to improve the performance of liquid crystal elements, improvements have been made to liquid crystal materials as well as liquid crystal alignment films for aligning liquid crystals in a certain direction (see, for example, Patent Document 1 and Patent Document 2).

[0003] Patent Document 1 discloses that a liquid crystal aligning agent containing a polyamic acid, which is a reaction product of a tetracarboxylic dianhydride and a diamine, and its derivatives is made to contain a polyamic acid obtained by using bis(5-aminobenzimidazole)benzene as a diamine in the liquid crystal aligning agent. Patent Document 2 discloses that a polyimide obtained by using N1,N4-bis[(2-tert-butoxycarbonylamino)-4-aminophenyl]adipamide as a diamine is made to contain in the liquid crystal aligning agent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-54872 A [Patent Document 2] International Publication No. 2014 / 104015 Summary of the Invention [Problem to be solved by the invention]

[0005] Monomers having a benzimidazole skeleton and polymers obtained using the monomers have low solubility and storage stability, and there is concern that the storage stability of the liquid crystal alignment agent is not good. In addition, the liquid crystal alignment film obtained using the liquid crystal alignment agent described in Patent Document 2 has low transmittance, and there is concern that the display quality is insufficient. Furthermore, liquid crystal elements are required to maintain a high voltage retention rate and be highly reliable even when used for a long period of time.

[0006] In addition, liquid crystal elements for smartphones and in-vehicle applications are required to be resistant to degradation of display quality caused by external forces and to have good touch panel characteristics, i.e., to achieve both touch panel resistance (also known as keystroke durability) and liquid crystal alignment.

[0007] The present invention has been made in consideration of the above problems, and has as its main object to provide a liquid crystal alignment agent that can form a liquid crystal alignment film having high transmittance, exhibits little decrease in voltage retention even when used over a long period of time, can produce a liquid crystal element having excellent touch panel resistance, and has good storage stability. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by introducing a specific partial structure into a polymer. Specifically, the present invention provides the following means.

[0009] <1> A liquid crystal aligning agent comprising a polymer [P] having at least one partial structure (A) selected from the group consisting of a partial structure represented by the following formula (1-1) and a partial structure represented by the following formula (1-2): [ka] (In formula (1-1) and formula (1-2), R 1 and R 4 R is a monovalent thermally labile group. 2 , R 3 , R 5 and R 6R is each independently a hydrogen atom or a monovalent organic group. 7 and R 8 are each independently a halogen atom or an alkyl group having 1 to 5 carbon atoms. n1 and n2 are each independently an integer of 0 to 3. When n1 is 2 or 3, multiple R 7 are the same or different. When n2 is 2 or 3, multiple R 8 are the same or different. X 1 is a single bond, -O-, -S-, -CO-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO-, * 1 -CO-NR 9 -, * 1 -NR 9 -CO-O- or -NR 9 -CO-NR 10 -It is. 9 and R 10 are each independently a hydrogen atom or a monovalent organic group. 1 " represents a bond to the benzene ring in the formula. 1 is an alkanediyl group having 1 to 10 carbon atoms. "*" represents a bond.

[0010] <2> the above <1> A liquid crystal alignment film formed using the liquid crystal alignment agent of the above. <3> the above <1> and a step of subjecting the coating film to a light irradiation treatment to impart liquid crystal aligning ability. <4> the above <2> A liquid crystal element comprising the liquid crystal alignment film.

[0011] <5> A polyamic acid, a polyamic acid ester, and a polyimide having a structural unit derived from at least one selected from the group consisting of a compound represented by the following formula (2-1) and a compound represented by the following formula (2-2): [ka] (In formula (2-1) and formula (2-2), R 1 and R 4 R is each independently a monovalent thermally detachable group. 2 , R 3 , R 5 and R 6 R is each independently a hydrogen atom or a monovalent organic group. 7 and R 8 are each independently a halogen atom or an alkyl group having 1 to 5 carbon atoms. n1 and n2 are each independently an integer of 0 to 3. When n1 is 2 or 3, multiple R 7 are the same or different. When n2 is 2 or 3, multiple R 8 are the same or different. X 1 is a single bond, -O-, -S-, -CO-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO-, * 1 -CO-NR 9 -, * 1 -NR 9 -CO-O- or -NR 9 -CO-NR 10 -It is. 9 and R 10 are each independently a hydrogen atom or a monovalent organic group. 1 " represents a bond to the benzene ring in the formula. 1 is an alkanediyl group having 1 to 10 carbon atoms. 1 , Y 2 , Y 3 and Y 4 are each independently a divalent organic group. 1 and B. 2 are each independently a single bond or an alkanediyl group having 1 to 10 carbon atoms.

[0012] <6> A compound represented by the above formula (2-1). <7> A compound represented by the above formula (2-2). Effect of the Invention

[0013] According to the liquid crystal aligning agent of the present invention, a liquid crystal alignment film having high transmittance can be formed. In addition, according to the liquid crystal aligning agent of the present invention, a liquid crystal element having high reliability and excellent touch panel resistance with little decrease in voltage holding ratio even when used for a long period of time can be manufactured. Furthermore, the liquid crystal aligning agent of the present invention has excellent storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Liquid crystal alignment agent Hereinafter, each component contained in the liquid crystal aligning agent of the present disclosure and other components that are optionally blended as necessary will be described.

[0015] In this specification, the term "hydrocarbon group" includes chain-shaped hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-shaped hydrocarbon group" means a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, they may be saturated or unsaturated. The term "alicyclic hydrocarbon group" means a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, it is not necessary to be composed only of an alicyclic hydrocarbon structure, and it also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" means a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it is not necessary to be composed only of an aromatic ring structure, and it may include a chain structure or an alicyclic hydrocarbon structure as a part of it. The term "aromatic ring" includes aromatic hydrocarbon rings and aromatic heterocycles. The term "organic group" means an atomic group obtained by removing any hydrogen atom from a compound containing carbon (i.e., an organic compound).

[0016] The liquid crystal aligning agent of the present disclosure contains a polymer [P] having at least one partial structure (A) selected from the group consisting of a partial structure represented by the following formula (1-1) and a partial structure represented by the following formula (1-2): [ka] (In formula (1-1) and formula (1-2), R 1and R 4 R is a monovalent thermally labile group. 2 , R 3 , R 5 and R 6 R is each independently a hydrogen atom or a monovalent organic group. 7 and R 8 are each independently a halogen atom or an alkyl group having 1 to 5 carbon atoms. n1 and n2 are each independently an integer of 0 to 3. When n1 is 2 or 3, multiple R 7 are the same or different. When n2 is 2 or 3, multiple R 8 are the same or different. X 1 is a single bond, -O-, -S-, -CO-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO-, * 1 -CO-NR 9 -, * 1 -NR 9 -CO-O- or -NR 9 -CO-NR 10 -It is. 9 and R 10 are each independently a hydrogen atom or a monovalent organic group. 1 " represents a bond to the benzene ring in the formula. 1 is an alkanediyl group having 1 to 10 carbon atoms. "*" represents a bond.

[0017] <Polymer [P]> (Substructure (A)) In the above formula (1-1) and formula (1-2), R 1 and R 4The monovalent thermally detachable group represented by is a group that is detached by heating and replaced with a hydrogen atom. Specific examples of the thermally detachable group include a tert-butoxycarbonyl group (Boc group), a benzyloxycarbonyl group, a 1,1-dimethyl-2-haloethyloxycarbonyl group, an allyloxycarbonyl group, and a 2-(trimethylsilyl)ethoxycarbonyl group. Among these, the Boc group is particularly preferred because it has excellent thermal detachability and can reduce the amount of the detached structure remaining in the film.

[0018] R 2 , R 3 , R 5 and R 6 The monovalent organic group represented by the formula (I) is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms or a monovalent thermally detachable group. 2 , R 3 , R 5 and R 6 When the group represented by R is a monovalent hydrocarbon group, the monovalent hydrocarbon group is preferably an alkyl group having 1 to 3 carbon atoms or a phenyl group, and more preferably an alkyl group having 1 to 3 carbon atoms. 2 , R 3 , R 5 and R 6 Specific examples of the group represented by the formula (I) are monovalent thermally eliminable groups, such as R 1 and R 4 Examples of the monovalent thermally detachable group represented by the following formula include the same groups as those exemplified above.

[0019] R 2 , R 3 , R 5 and R 6 When the group represented by the formula (I) is a monovalent organic group, the monovalent organic group is preferably an alkyl group having 1 to 3 carbon atoms or a thermally eliminable group among the above, and more preferably an alkyl group having 1 to 3 carbon atoms or a tert-butoxycarbonyl group.

[0020] In order to facilitate the intramolecular cyclization reaction by heating during film formation, R 2 , R 3 , R 5 and R 6is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally dissociable group, more preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a tert-butoxycarbonyl group, and particularly preferably a hydrogen atom.

[0021] R 7 and R 8 In the above formula, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group having 1 to 5 carbon atoms may be linear or branched. 7 and R 8 The group represented by the following formula is preferably a halogen atom or an alkyl group having 1 to 3 carbon atoms. Each of n1 and n2 is preferably 0 or 1, and more preferably 0.

[0022] X 1 The group represented by -NR 9 -, * 1 -NR 9 -CO-, * 1 -CO-NR 9 -, * 1 -NR 9 -CO-O- or -NR 9 -CO-NR 10 -If R 9 and R 10 In the above, the monovalent organic group is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms or a monovalent thermally eliminable group. Specific examples of the monovalent hydrocarbon group having 1 to 10 carbon atoms include an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms. Of these, an alkyl group and a phenyl group having 1 to 3 carbon atoms are preferred, and an alkyl group having 1 to 3 carbon atoms is more preferred.

[0023] R 9 and R 10 Specific examples of the monovalent organic group represented by the formula (I) are monovalent thermally eliminable groups, such as R 1 and R 4 Among these, the Boc group is particularly preferred because it is easily removable by heat and can minimize the amount of the removed structure remaining in the film. 9and R 10 is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group, and more preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a tert-butoxycarbonyl group.

[0024] X 1 From the viewpoint of obtaining a liquid crystal element exhibiting good liquid crystal alignment property and from the viewpoint of ease of synthesis of the skeleton constituting the partial structure (A), -O-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO- or * 1 -CO-NR 9 - is preferred.

[0025] A 1 The alkanediyl group having 1 to 10 carbon atoms represented by the formula (I) may be linear or branched. A is preferable in that it can form a liquid crystal alignment film having a high film density, a high effect of improving the voltage retention characteristic and the touch panel resistance, and a liquid crystal alignment film in which coloring is suppressed. 1 is preferably a linear alkanediyl group. 1 The number of carbon atoms is preferably 6 or less, and more preferably 3 or less, from the viewpoint of obtaining a liquid crystal element exhibiting a high voltage holding ratio and a liquid crystal element exhibiting good liquid crystal alignment properties.

[0026] From the viewpoint of increasing the density of the film, it is preferable that the carbonyl group in the above formula (1-1) and formula (1-2) is bonded to a saturated chain hydrocarbon structure. Specifically, it is preferable that the polymer [P] has at least one selected from the group consisting of a partial structure represented by the following formula (3-1) and a partial structure represented by the following formula (3-2). [ka] (In the formula (3-1) and the formula (3-2), D 1 and D. 2 R is each independently an alkanediyl group having 1 to 10 carbon atoms. 1 , R 2 , R3 , R 4 , R 5 , R 6 , R 7 , R 8 , n1, n2, X 1 and A 1 has the same meaning as the above formula (1-1) and formula (1-2).

[0027] In the above formula (1-1) and formula (1-2), D 1 and D. 2 The alkanediyl group having 1 to 10 carbon atoms represented by the formula (I) may be linear or branched. D is advantageous in that it is possible to form a liquid crystal alignment film having a high film density and a high effect of improving voltage retention characteristics and touch panel resistance, and in that it is possible to form a liquid crystal alignment film in which coloring is suppressed. 1 and D. 2 is preferably a linear alkanediyl group.

[0028] The polymer [P] preferably has a partial structure (A) in its main chain, since it can suppress the deterioration of display quality even when an external force is applied by tapping or the like, and has a high effect of improving touch panel resistance. From the viewpoint of ease of synthesis of a polymer having the partial structure (A) in its main chain, the polymer [P] can be preferably produced by a method of polymerization using a monomer having the partial structure (A). The monomer having the partial structure (A) is preferably a diamine compound having the partial structure (A) (hereinafter also referred to as a "specific diamine"), since it can form a liquid crystal alignment film having high affinity with liquid crystal and high mechanical strength, and there is a high degree of freedom in selecting the monomer.

[0029] In this specification, the "main chain" of a polymer refers to the "trunk" portion of the polymer, which is the longest chain of atoms. It is permissible for this "trunk" portion to contain a ring structure. In other words, when a polymer "has partial structure (A) in its main chain," this means that partial structure (A) constitutes a part of the main chain of the polymer. The "side chain" of a polymer refers to a portion branched off from the "trunk" of the polymer.

[0030] (Specific diamine) The specific diamine may be a monomer having the partial structure (A) and two primary amino groups, and the structure of the other parts is not particularly limited. A preferred specific example of the specific diamine is at least one selected from the group consisting of the compounds represented by the following formula (2-1) and the compounds represented by the following formula (2-2). [ka] (In formula (2-1) and formula (2-2), Y 1 , Y 2 , Y 3 and Y 4 are each independently a divalent organic group. 1 and B. 2 R are each independently a single bond or an alkanediyl group having 1 to 10 carbon atoms. 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , n1, n2, X 1 and A 1 has the same meaning as the above formula (1-1) and formula (1-2).

[0031] In the above formula (2-1) and formula (2-2), Y 1 , Y 2 , Y 3 and Y 4 Examples of the divalent organic group represented by the formula (I) include a divalent chain group and a cyclic group, and a divalent cyclic group is preferred. Examples of the divalent cyclic group include a divalent alicyclic group and an aromatic ring group.

[0032] Examples of the divalent alicyclic group include groups obtained by removing two hydrogen atoms from an alicyclic hydrocarbon ring such as a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, or a cycloheptane ring. In the divalent alicyclic group, a substituent may be introduced into the ring portion of the alicyclic hydrocarbon ring. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen atom.

[0033] The divalent aromatic ring group includes a divalent aromatic hydrocarbon ring group and an aromatic heterocyclic group, and preferably includes a divalent aromatic hydrocarbon ring group and a nitrogen-containing aromatic heterocyclic group. Specific examples of these include a divalent aromatic hydrocarbon ring group obtained by removing any hydrogen atom bonded to a carbon atom constituting a ring of a benzene ring, a biphenyl ring, a naphthalene ring, or an anthracene ring; and a divalent nitrogen-containing aromatic heterocyclic group obtained by removing any two hydrogen atoms bonded to a carbon atom constituting a ring of a pyridine ring, a pyrimidine ring, a pyridazine ring, or a pyrazine ring. In the divalent aromatic ring group, a substituent may be introduced into the ring portion of the aromatic ring. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen atom.

[0034] From the viewpoint of increasing the density of the liquid crystal alignment film, Y 1 , Y 2 , Y 3 and Y 4 The divalent organic group represented by the formula (I) is preferably a divalent aromatic hydrocarbon ring group or a nitrogen-containing aromatic heterocyclic group, more preferably a substituted or unsubstituted phenylene group, biphenylene group, or pyridinediyl group, and further preferably a substituted or unsubstituted phenylene group.

[0035] B 1 and B. 2 At least one of B is preferably an alkanediyl group having 1 to 10 carbon atoms; 1 and B. 2 More preferably, both are alkanediyl groups having 1 to 10 carbon atoms. 1 and B. 2 The alkanediyl group having 1 to 10 carbon atoms represented by the formula (I) may be linear or branched. B is preferred because it is possible to form a liquid crystal alignment film having a high density and a high effect of improving the voltage retention property and the touch panel resistance, and because it is possible to form a liquid crystal alignment film in which coloring is suppressed. 1 and B. 2 is preferably a linear alkanediyl group. 1 and B. 2The number of carbon atoms is preferably 6 or less, and more preferably 3 or less, from the viewpoint of obtaining a liquid crystal element exhibiting a high voltage holding ratio and a liquid crystal element exhibiting good liquid crystal alignment properties.

[0036] Specific examples of the specific diamine include compounds represented by the following formulas (4-1) to (4-12), in which "Boc" represents a tert-butoxycarbonyl group (the same applies hereinafter). [ka] [ka]

[0037] In the polymer [P], the content of the structural unit (hereinafter also referred to as "structural unit (UA)") derived from a monomer having a partial structure (A) is preferably 2 mol% or more relative to the total amount of monomer units contained in the polymer [P] (100 mol%), from the viewpoint of obtaining a liquid crystal element that exhibits a high voltage holding ratio (VHR), has little decrease in voltage holding ratio even when used for a long period of time, and has excellent touch panel resistance. The content of the structural unit (UA) is more preferably 5 mol% or more, and even more preferably 7 mol% or more, relative to the total amount of monomer units contained in the polymer [P]. In addition, the content of the structural unit (UA) can be appropriately set according to the main chain of the polymer [P], but when the polymer [P] is obtained by condensation polymerization, it is, for example, 50 mol% or less relative to the total amount of monomer units contained in the polymer [P]. The structural unit (UA) contained in the polymer [P] may be only one type, or may be two or more types.

[0038] The specific diamine can be synthesized by appropriately combining the standard methods of organic chemistry. One example of the synthesis method is to synthesize a dinitro intermediate having a nitro group instead of the primary amino group in the above formula (2-1) and the above formula (2-2), and then animate the nitro group of the obtained dinitro intermediate using a suitable reduction system.

[0039] The method for synthesizing the dinitro intermediate is not particularly limited, and can be appropriately selected from condensation reaction between carboxylic acid and amine, condensation reaction between carboxylic acid and alcohol, condensation reaction between carboxylic acid and phenol, etc., depending on the target compound. A specific example of synthesis in which the dinitro intermediate is obtained by utilizing the condensation reaction between carboxylic acid and amine is shown below. [ka] (In the scheme, Z 1 is an alkanediyl group. [ka] (In the scheme, Z 1 is an alkanediyl group.

[0040] The reduction reaction of the dinitro intermediate can be preferably carried out in an organic solvent using a catalyst such as palladium on carbon, platinum oxide, zinc, iron, tin, nickel, platinum on carbon, or osmium on carbon. Examples of the organic solvent used here include ethyl acetate, toluene, tetrahydrofuran, and alcohols. Two or more of these organic solvents may be mixed and used. However, the synthesis procedure of the compound represented by the above formula (2-1) and the compound represented by the above formula (2-2) is not limited to the above method.

[0041] (Production of polymer [P]) The main chain of the polymer [P] is not particularly limited. In terms of being able to form a liquid crystal alignment film having high affinity with liquid crystals and mechanical strength and high reliability, the polymer [P] is preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.

[0042] (Polyamic acid) When the polymer [P] is a polyamic acid, the polyamic acid (hereinafter also referred to as "polyamic acid [P]") can be obtained by reacting a tetracarboxylic dianhydride with a diamine compound containing a specific diamine.

[0043] (Tetracarboxylic acid dianhydride) Examples of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P] include aliphatic tetracarboxylic dianhydrides, alicyclic tetracarboxylic dianhydrides, and aromatic tetracarboxylic dianhydrides. Specific examples of these include aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride and ethylenediaminetetraacetic dianhydride; alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8-tetracarboxybiphenyl ether, and the like. Examples of the tetracarboxylic dianhydride include cyclo[3.3.0]octane-2:4,6:8-dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane tetracarboxylic dianhydride, and 3,5,6-tricarboxy-2-carboxymethylnorbornane-2:3,5:6-dianhydride; examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, ethylene glycol bisanhydrotrimate, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, and 3,3',4,4'-biphenyl tetracarboxylic dianhydride; and examples of the tetracarboxylic dianhydride disclosed in JP-A-2010-97188 can be used. As the tetracarboxylic dianhydride, one type can be used alone or two or more types can be used in combination.

[0044] The tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P] preferably contains at least one selected from the group consisting of an aliphatic tetracarboxylic dianhydride and an alicyclic tetracarboxylic dianhydride, and more preferably contains an alicyclic tetracarboxylic dianhydride, in that a liquid crystal alignment film having high solubility and exhibiting good liquid crystal alignment properties and electrical properties can be obtained. The proportion of the alicyclic tetracarboxylic dianhydride used is preferably 5 mol % or more, more preferably 10 mol % or more, and even more preferably 20 mol % or more, based on the total amount of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P].

[0045] (Diamine compounds) The diamine compound used in the synthesis of the polyamic acid [P] may be the specific diamine alone, or may be a diamine not having the partial structure (A) (hereinafter, also referred to as "other diamines") in addition to the specific diamine. Examples of other diamines include aliphatic diamines, alicyclic diamines, aromatic diamines, and diaminoorganosiloxanes.

[0046] Specific examples of other diamines include aliphatic diamines such as metaxylylenediamine and hexamethylenediamine; alicyclic diamines such as 1,4-diaminocyclohexane and 4,4'-methylenebis(cyclohexylamine); and aromatic diamines such as p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4-aminophenyl-4-aminobenzoate, 4,4'-diaminoazobenzene, 3,5-diaminobenzoic acid, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1,6-bis(4-aminophenoxy)hexane, 6,6'-(pentamethylenedioxy)bis(3-aminopyridine), N,N'-di(5-amino-2-pyridyl)-N,N'-di(t ert-butoxycarbonyl)ethylenediamine, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylamine, 4,4'-diaminodiphenethyl urea, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-(phenylenediisopropylidene)bisaniline, 2,6-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, 3,6-diaminoacridine, diphenylamine structure-containing monomer, the following formula (D-1): [ka] (In formula (D-1), R 11 and R 12 are each independently an alkanediyl group. 13 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. n3 is an integer of 1 to 3. When n3 is 2 or 3, multiple R 12 are the same or different, and multiple R 13 are the same or different.) Main chain diamines such as compounds represented by the following formula: Hexadecanoxy-2,4-diaminobenzene, Octadecanoxy-2,4-diaminobenzene, Octadecanoxy-2,5-diaminobenzene, Cholestanylooxy-3,5-diaminobenzene, Cholesteryloxy-3,5-diaminobenzene, Cholestanylooxy-2,4-diaminobenzene, Cholesteryloxy-2,4-diaminobenzene, Cholestanylo 3,5-diaminobenzoate, Cholesteryl 3,5-diaminobenzoate , lanostannyl 3,5-diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, 3,6-bis(4-aminophenoxy)cholestane, 4-(4'-trifluoromethoxybenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-butylcyclohexane, 3,5-diaminobenzoic acid = 5ξ-cholestan-3-yl, the following formula (E-1): [ka] (In formula (E-1), X I and X II are each independently a single bond, -O-, *-COO- or *-OCO- (where "*" represents X I It shows the bond with . ) R I R is an alkanediyl group having 1 to 3 carbon atoms. II R is a single bond or an alkanediyl group having 1 to 3 carbon atoms. III is an alkyl group, an alkoxy group, a fluoroalkyl group, or a fluoroalkoxy group having 1 to 20 carbon atoms. a is 0 or 1. b is an integer of 0 to 3. c is an integer of 0 to 2. d is 0 or 1, provided that 1≦a+b+c≦3. A side chain type diamine such as a compound represented by the formula: Examples of diaminoorganosiloxanes include 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, and the like.

[0047] Examples of the diphenylamine structure-containing monomer include compounds represented by the following formulae (C-1-1) to (C-1-8). Examples of the compound represented by the above formula (D-1) include compounds represented by the following formulae (D-1-1) to (D-1-3). Examples of the compound represented by the above formula (E-1) include compounds represented by the following formulae (E-1-1) to (E-1-4). As the other diamines, one type may be used alone or two or more types may be used in combination. [ka] [ka]

[0048] In the synthesis of the polyamic acid [P], the proportion of the specific diamine used is preferably 5 mol % or more, more preferably 10 mol % or more, and even more preferably 15 mol % or more, based on the total amount of the diamine compounds used in the synthesis of the polyamic acid [P], from the viewpoint of obtaining a liquid crystal element that exhibits high VHR, has little VHR decrease even when used for a long period of time, and is excellent in touch panel resistance. As the specific diamine, one type may be used alone, or two or more types may be used in combination.

[0049] (Synthesis of polyamic acid) The polyamic acid [P] can be obtained by reacting a tetracarboxylic dianhydride with a diamine compound, optionally together with a molecular weight modifier. In the synthesis reaction of the polyamic acid [P], the ratio of the tetracarboxylic dianhydride to the diamine compound is preferably such that the acid anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents per equivalent of the amino group of the diamine compound. Examples of the molecular weight modifier include acid monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride, monoamine compounds such as aniline, cyclohexylamine, and n-butylamine, and monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate. The ratio of the molecular weight modifier to be used is preferably 20 parts by mass or less per 100 parts by mass of the total of the tetracarboxylic dianhydride and diamine compound used.

[0050] The synthesis reaction of the polyamic acid [P] is preferably carried out in an organic solvent. The reaction temperature is preferably -20°C to 150°C, and the reaction time is preferably 0.1 to 24 hours. Examples of the organic solvent used in the reaction include aprotic polar solvents, phenolic solvents, alcoholic solvents, ketone solvents, ester solvents, ether solvents, halogenated hydrocarbons, and hydrocarbons. Specific examples of these include one or more selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphortriamide, m-cresol, xylenol, and halogenated phenols, or a mixture of one or more of these with another organic solvent (e.g., butyl cellosolve, diethylene glycol diethyl ether, etc.). The amount of the organic solvent used is preferably an amount such that the total amount of the tetracarboxylic dianhydride and the diamine is 0.1 to 50 mass% relative to the total amount of the reaction solution.

[0051] In this manner, a polymer solution in which the polyamic acid [P] is dissolved is obtained. This polymer solution may be used as it is for the preparation of a liquid crystal alignment agent, or the polyamic acid [P] contained in the polymer solution may be isolated and then used for the preparation of a liquid crystal alignment agent.

[0052] Polyamic acid ester When the polymer [P] is a polyamic acid ester, the polyamic acid ester (hereinafter also referred to as "polyamic acid ester [P]") can be obtained, for example, by a method of reacting a polyamic acid [P] with an esterifying agent, a method of reacting a tetracarboxylic acid diester with a diamine compound containing a specific diamine, or a method of reacting a tetracarboxylic acid diester dihalide with a diamine compound containing a specific diamine. The polyamic acid ester [P] may have only an amic acid ester structure, or may be a partially esterified product in which an amic acid structure and an amic acid ester structure coexist. The reaction solution in which the polyamic acid ester [P] is dissolved may be used as it is for the preparation of a liquid crystal alignment agent, or the polyamic acid ester [P] contained in the reaction solution may be isolated and then used for the preparation of a liquid crystal alignment agent.

[0053] Polyimide When the polymer [P] is a polyimide, the polyimide (hereinafter also referred to as "polyimide [P]") can be obtained, for example, by dehydrating and cyclizing the polyamic acid [P] synthesized as described above to convert it into an imidized product. The polyimide [P] may be a complete imidized product in which all of the amic acid structures of the precursor polyamic acid [P] are dehydrated and cyclized, or a partial imidized product in which only a part of the amic acid structures are dehydrated and cyclized, and an amic acid structure and an imide ring structure coexist. The polyimide [P] preferably has an imidization rate of 20 to 99%, more preferably 30 to 90%. The imidization rate is the ratio of the number of imide ring structures to the total number of amic acid structures and the number of imide ring structures of the polyimide, expressed as a percentage. Here, a part of the imide rings may be isoimide rings.

[0054] The dehydration ring-closing of the polyamic acid [P] is preferably carried out by dissolving the polyamic acid [P] in an organic solvent, adding a dehydrating agent and a dehydration ring-closing catalyst to the solution, and heating as necessary. In this method, the dehydrating agent may be, for example, an acid anhydride such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride. The amount of the dehydrating agent used is preferably 0.01 to 20 moles per mole of the amic acid structure of the polyamic acid [P]. The dehydration ring-closing catalyst may be, for example, a tertiary amine such as pyridine, collidine, lutidine, or triethylamine. The amount of the dehydration ring-closing catalyst used is preferably 0.01 to 10 moles per mole of the dehydrating agent used. The organic solvent used in the dehydration ring-closing reaction may be the organic solvent exemplified as the one used in the synthesis of the polyamic acid [P]. The reaction temperature in the dehydration ring-closing reaction is preferably 0 to 180° C. The reaction time is preferably 1.0 to 120 hours. The reaction solution containing the polyimide [P] may be used for the preparation of a liquid crystal aligning agent as it is, or the polyimide [P] may be isolated and then used for the preparation of a liquid crystal aligning agent.

[0055] The solution viscosity of the polymer [P] used in preparing the liquid crystal alignment agent is preferably 10 to 800 mPa·s when made into a 10% by mass solution, and more preferably 15 to 500 mPa·s. The solution viscosity (mPa·s) is a value measured at 25°C using an E-type rotational viscometer for a 10% by mass polymer solution prepared using a good solvent for the polymer [P] (e.g., γ-butyrolactone, N-methyl-2-pyrrolidone, etc.).

[0056] The weight average molecular weight (Mw) of the polymer [P] in terms of polystyrene measured by gel permeation chromatography (GPC) is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn) expressed as the ratio of Mw to the number average molecular weight (Mn) in terms of polystyrene measured by GPC is preferably 7 or less, more preferably 5 or less. In preparing the liquid crystal aligning agent, the polymer [P] may be used alone or in combination of two or more.

[0057] <Other ingredients> The liquid crystal aligning agent may contain, in addition to the polymer [P], components different from the polymer [P] (hereinafter also referred to as "other components"), if necessary.

[0058] Polymer [Q] The liquid crystal alignment agent of the present disclosure may further contain a polymer (hereinafter also referred to as "polymer [Q]") that does not have a partial structure (A) as a polymer component. The main skeleton of the polymer [Q] is not particularly limited. Examples of other polymers include polyamic acid, polyamic acid ester, polyimide, polyorganosiloxane, polyester, polyenamine, polyurea, polyamide, polyamideimide, polybenzoxazole precursor, polybenzoxazole, cellulose derivative, polyacetal, (meth)acrylic polymer, styrene polymer, maleimide polymer, styrene-maleimide copolymer, etc.

[0059] From the viewpoint of obtaining a highly reliable liquid crystal element, the polymer [Q] is preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, polyimide, polyorganosiloxane, and polymers containing a structural unit derived from a monomer having a polymerizable unsaturated carbon-carbon bond. Examples of polymers containing a structural unit derived from a monomer having a polymerizable unsaturated carbon-carbon bond include (meth)acrylic polymers, styrene polymers, maleimide polymers, and styrene-maleimide copolymers. Among these, the polymer [Q] is particularly preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.

[0060] When the polymer [Q] is contained in the liquid crystal alignment agent, the content of the polymer [Q] is preferably 1% by mass or more, more preferably 2% by mass or more, based on the total amount of the polymer [P] and the polymer [Q]. The content of the polymer [Q] is preferably 95% by mass or less, more preferably 90% by mass or less, based on the total amount of the polymer [P] and the polymer [Q]. The polymer [Q] may be used alone or in combination of two or more kinds.

[0061] ·solvent The liquid crystal aligning agent of the present disclosure is prepared as a liquid composition in which the polymer [P] and other components used as necessary are preferably dispersed or dissolved in a suitable solvent.

[0062] As the solvent, an organic solvent is preferably used.Specific examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, 1,3-dimethyl-2-imidazolidinone, phenol, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, diacetone alcohol, 1-hexanol, 2-hexanol, propane-1,2-diol, 3-methoxy-1-butanol, ethylene glycol monomethyl ether, methyl lactate, ethyl lactate, butyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, ethyl acetoacetate, ethyl propionate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, and ethylene glycol-i-propyl ether. Examples of the solvent include ethylene glycol-n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, propylene carbonate, propylene glycol monomethyl ether (PGME), diethylene glycol diethyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol diacetate, cyclopentanone, cyclohexanone, etc. As the solvent, one type can be used alone or two or more types can be mixed and used.

[0063] Other components contained in the liquid crystal alignment agent include, in addition to the above, for example, a crosslinking agent, an antioxidant, a metal chelate compound, a curing accelerator, a surfactant, a filler, a dispersant, a photosensitizer, etc. The blending ratio of the other components can be appropriately selected according to each compound within a range that does not impair the effects of the present disclosure.

[0064] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass %. If the solid content concentration is 1 mass % or more, it is preferable in that the thickness of the coating film can be sufficiently ensured and a liquid crystal alignment film exhibiting better liquid crystal alignment properties can be obtained. On the other hand, if the solid content concentration is 10 mass % or less, the coating film can be made to have an appropriate thickness, making it easier to obtain a liquid crystal alignment film exhibiting good liquid crystal alignment properties, and the viscosity of the liquid crystal alignment agent becomes appropriate, tending to improve the coatability.

[0065] <Liquid crystal alignment film and liquid crystal element> The liquid crystal alignment film of the present disclosure is manufactured by the liquid crystal alignment agent prepared as described above. The liquid crystal element of the present disclosure includes a liquid crystal alignment film formed by using the liquid crystal alignment agent described above. The driving method of the liquid crystal in the liquid crystal element is not particularly limited, and can be applied to various modes such as TN type, STN type, VA type (including VA-MVA type, VA-PVA type, etc.), IPS type, FFS type, OCB (Optically Compensated Bend) type, PSA (Polymer Sustained Alignment) type, etc. The liquid crystal element can be manufactured by a method including, for example, the following steps 1 to 3. In step 1, the substrate used differs depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.

[0066] <Step 1: Formation of coating film> First, a liquid crystal alignment agent is applied onto a substrate, and a coating film is formed on the substrate, preferably by heating the applied surface. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass; or plastic such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, or poly(alicyclic olefin) can be used. As the transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of US PPG) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), or the like can be used. When manufacturing a TN-type, STN-type, or VA-type liquid crystal element, two substrates on which a patterned transparent conductive film is provided are used. On the other hand, when manufacturing an IPS-type or FFS-type liquid crystal element, a substrate on which an electrode patterned in a comb-tooth shape is provided and an opposing substrate on which no electrode is provided are used.

[0067] The method of applying the liquid crystal alignment agent to the substrate is not particularly limited. The liquid crystal alignment agent can be applied to the substrate by, for example, a spin coat method, a printing method (for example, an offset printing method, a flexographic printing method, etc.), an inkjet method, a slit coat method, a bar coater method, an extrusion die method, a direct gravure coater method, a chamber doctor coater method, an offset gravure coater method, an impregnation coater method, an MB coater method, etc.

[0068] After the liquid crystal alignment agent is applied, preheating (prebaking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent. The prebaking temperature is preferably 30 to 200° C., and the prebaking time is preferably 0.25 to 10 minutes. Thereafter, the solvent is completely removed, and a baking (postbaking) step is performed, if necessary, for the purpose of thermally imidizing the amic acid structure present in the polymer. The baking temperature (postbaking temperature) at this time is preferably 80 to 280° C., more preferably 80 to 250° C. The postbaking time is preferably 5 to 200 minutes. The thickness of the film formed is preferably 0.001 to 1 μm.

[0069] <Step 2: Alignment Treatment> When manufacturing a TN-type, STN-type, IPS-type or FFS-type liquid crystal element, the coating film formed in the above step 1 is subjected to a treatment (alignment treatment) for imparting liquid crystal alignment ability. This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. As the alignment treatment, it is preferable to use a rubbing treatment in which the surface of the coating film formed on the substrate is rubbed with cotton, nylon or the like, or a photo-alignment treatment in which the coating film is irradiated with light to impart liquid crystal alignment ability. When manufacturing a vertical alignment type liquid crystal element, the coating film formed in the above step 1 may be used as it is as a liquid crystal alignment film, or the coating film may be subjected to an alignment treatment in order to further enhance the liquid crystal alignment ability.

[0070] The light irradiation for photo-alignment can be performed by a method of irradiating the coating film after the post-bake step, a method of irradiating the coating film after the pre-bake step but before the post-bake step, or a method of irradiating the coating film during heating in at least one of the pre-bake step and the post-bake step. For example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used as the radiation to be irradiated to the coating film. Preferably, ultraviolet light containing light with a wavelength of 200 to 400 nm is used. When the radiation is polarized, it may be linearly polarized or partially polarized. When the radiation used is linearly polarized or partially polarized, the radiation may be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When the radiation is non-polarized, the radiation is irradiated in an oblique direction.

[0071] Examples of the light source used include a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. The radiation dose is preferably 200 to 30,000 J / m 2 and more preferably 500 to 10,000 J / m 2After the light irradiation for imparting the alignment ability, the surface of the substrate may be washed with, for example, water, an organic solvent (e.g., methanol, isopropyl alcohol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, etc.) or a mixture thereof, or the substrate may be heated.

[0072] <Step 3: Construction of liquid crystal cell> Two substrates on which the liquid crystal alignment film is formed are prepared as described above, and a liquid crystal is placed between the two substrates arranged opposite to each other to manufacture a liquid crystal cell. For example, the liquid crystal cell can be manufactured by placing two substrates opposite to each other with a gap therebetween so that the liquid crystal alignment film faces each other, bonding the peripheries of the two substrates with a sealant, injecting liquid crystal into the cell gap surrounded by the substrate surfaces and the sealant, and sealing the injection hole, or by a method using the ODF method. For example, an epoxy resin containing a hardener and aluminum oxide spheres as a spacer can be used as the sealant. For example, a nematic liquid crystal or a smectic liquid crystal can be used as the liquid crystal, and among these, a nematic liquid crystal is preferable.

[0073] When manufacturing a liquid crystal display device, a polarizing plate is subsequently attached to the outer surface of the liquid crystal cell. Examples of the polarizing plate include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, and a polarizing plate made of the H film itself.

[0074] Here, when a liquid crystal alignment film is formed by applying a liquid crystal alignment agent containing the polymer [P] having the partial structure (A) onto a substrate and heating it, the thermally detachable group (R 1 , R 4) is eliminated, and a cyclization reaction occurs between the carbonyl group and the nitrogen-containing functional group in the above formula (1-1) or (1-2), forming a benzimidazole ring structure. When contained in a liquid crystal aligning agent, such a polymer [P] does not contain a benzimidazole ring structure, and has good solubility and good storage stability of the liquid crystal aligning agent. On the other hand, when heated during film formation, the polymer [P] undergoes a cyclization reaction within the molecule, which is thought to result in the formation of a benzimidazole ring structure in the polymer [P]. In addition, the thermally detachable group (R 1 , R 4 It is believed that some of the functional groups generated by the elimination of the polymer [P] contribute to the crosslinking reaction between molecules. As a result, it is believed that the liquid crystal alignment film formed using the liquid crystal alignment agent containing the polymer [P] exhibits high VHR, and the decrease in VHR is small even when used for a long period of time, and liquid crystal elements with excellent touch panel resistance can be obtained.

[0075] The liquid crystal element of the present disclosure can be effectively applied to various applications, specifically, for example, it can be used as various display devices such as clocks, portable game machines, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as light control devices, retardation films, and the like. EXAMPLES

[0076] Hereinafter, the embodiments will be described in more detail with reference to examples, but the present invention should not be construed as being limited to the following examples.

[0077] In the following examples, the purity of the monomer, the weight average molecular weight (Mw) of the polymer, the number average molecular weight (Mn) of the polymer, the imidization rate of the polyimide in the polymer solution, and the solution viscosity of the polymer solution were measured by the following methods. The required amounts of the raw material compounds and polymers used in the following examples were ensured by repeating the synthesis on a synthesis scale shown in the following synthesis examples as necessary. [Monomer purity] The purity of the monomer (LC purity) was measured by high performance liquid chromatography under the following conditions. Column: AGILENT ZORBAX Eclipse XDB C18 Solvent: A mixture of 70% tetrahydrofuran and 30% water containing ammonium acetate Temperature: 40℃ [Weight average molecular weight (Mw) and number average molecular weight (Mn) of polymer] Mw and Mn are values ​​calculated as polystyrene equivalents measured by GPC under the following conditions. Column: TSKgelGRCXLII, manufactured by Tosoh Corporation Solvent: Lithium bromide and phosphoric acid in N,N-dimethylformamide Temperature: 40℃ Pressure: 68kgf / cm 2 [Imidization rate of polyimide] The polyimide solution was poured into pure water, and the resulting precipitate was thoroughly dried under reduced pressure at room temperature. It was then dissolved in deuterated dimethyl sulfoxide and measured at room temperature using tetramethylsilane as a standard substance. 1 H-NMR measurement was performed. 1 The imidization rate [%] was calculated from the H-NMR spectrum using the following formula (1). Imidization rate [%] = (1-(A 1 / (A 2 ×α)))×100 …(1) (In formula (1), A 1 is the peak area due to the proton of the NH group that appears at a chemical shift of around 10 ppm, and A 2 is the peak area due to other protons, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid).

[0078] The abbreviations of the compounds are as follows: In the following, the compound represented by formula (X) may be simply referred to as "compound (X)". (Tetracarboxylic acid dianhydride) [ka]

[0079] (Diamine compounds) [ka] [ka] [ka]

[0080] <Synthesis of Monomer> [Synthesis Example 1A] Diamine (DA-1) was synthesized according to the following scheme. [ka]

[0081] In a three-neck flask equipped with a nitrogen inlet tube, 2,5-diamino-tert-butoxycarbonylaminobenzene (0.61 g), 4-nitrohydrocinnamic acid (1.18 g), and 4-dimethylaminopyridine (18.1 mg) were placed and replaced with nitrogen, and 4 mL of dichloromethane was added and stirred under a nitrogen atmosphere. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (1.32 g) dispersed in 6.5 mL of dichloromethane was added dropwise thereto and stirred at room temperature for 12 hours. After the reaction was completed, 10 mL of water was added to the reaction solution and stirred, and the organic layer was concentrated to precipitate the product. The obtained aqueous dispersion was filtered, and the crude product was washed with water and 2-propanol and dried in vacuum to obtain a white powder of a nitro intermediate product (1.50 g, yield 94%). Next, 0.75 g of palladium carbon was placed in a three-neck flask equipped with a reflux tube and a nitrogen inlet tube, and the atmosphere was replaced with nitrogen. 10 mL of tetrahydrofuran that had been degassed by nitrogen bubbling and 2.5 mL of ethanol were placed therein, and the nitro intermediate product (1.50 g) was added, followed by stirring to obtain a suspension solution. 0.76 mL of hydrazine monohydrate was slowly added dropwise to the reaction solution at room temperature. After the dropwise addition, the temperature was gradually raised to 60°C and stirred for 4 hours. The reaction solution was diluted with 10 mL of tetrahydrofuran, filtered through Celite, and concentrated to precipitate the product. The resulting precipitate was washed with water and 2-propanol and dried in vacuum to obtain a white solid diamine (DA-1) (1.00 g, yield 75%). Its structure is shown in the nuclear magnetic resonance spectrum of the intramolecular hydrogen atom. 1 The measurement data is shown below. 1 H-NMR(400MHz,[D6]-DMSO)δ:9.88(s, 1H), 9.37(s, 1H), 8.30(s, 1H), 7.81(d, 1H), 7.37(dd, 1H) , 7.21(d, 1H), 6.88(dd, 4H), 6.48(dd, 4H), 4.83(d, 4H), 2.72(m, 4H), 2.51(m, 4H), 1.45(s, 9H).

[0082] <Monomer evaluation> [Evaluation Example 1-1: Evaluation of storage stability and coloration] 1 g of diamine (DA-1) was placed in a screw tube and stored at 60°C for one month, after which the LC purity and the presence or absence of coloration were observed. If the decrease in LC purity was less than 1%, it was rated as "good (○)", if it was between 1% and less than 5%, it was rated as "passable (△)", and if it was 5% or more, it was rated as "poor (×)". In addition, if there was no coloration, it was rated as "good (○)", and if there was coloration, it was rated as "poor (×)". As a result, both the LC purity and coloration of this evaluation example were "good (○)".

[0083] [Evaluation Example 1-2, Comparative Evaluation Examples 1-1 to 1-4, and Reference Evaluation Example 1-1] The storage stability and coloration of the diamine were evaluated in the same manner as in Evaluation Example 1-1, except that the diamine to be evaluated was changed as shown in Table 1. The results are shown in Table 1.

[0084] [Table 1]

[0085] As shown in Table 1, the specific diamines having the partial structure (A) (Evaluation Examples 1-1 and 1-2) were better in at least one of the reduction in LC purity and coloration than the diamines of Comparative Evaluation Examples 1-1 to 1-4.

[0086] <Polymer synthesis> 1. Synthesis of polyamic acid [Synthesis example 1B] 100 parts by mole of compound (TA-1) as a tetracarboxylic dianhydride and 100 parts by mole of compound (DB-1) as a diamine compound were dissolved in N-methyl-2-pyrrolidone (NMP) and reacted at room temperature for 6 hours to obtain a solution containing 15% by mass of polyamic acid (referred to as polymer (PA-1)).

[0087] [Synthesis examples 2B to 16B] Polyamic acids (polymers (PA-2) to (PA-16)) were obtained by the same procedure as in Synthesis Example 1B, except that the types and amounts of the tetracarboxylic dianhydrides and diamine compounds used were changed as shown in Tables 2 and 3. In Tables 2 and 3, the numerical values ​​for the acid anhydrides indicate the proportion (parts by mole) of each compound used relative to a total of 100 parts by mole of the tetracarboxylic dianhydrides used in the synthesis of the polymers. The numerical values ​​for the diamines indicate the proportion (parts by mole) of each compound used relative to a total of 100 parts by mole of the diamine compounds used in the synthesis of the polymers (the same applies to Table 4).

[0088] [Table 2]

[0089] [Table 3]

[0090] 2. Synthesis of Polyimide [Synthesis example 17B] 100 mol parts of compound (TA-2) as tetracarboxylic dianhydride, 30 mol parts of compound (DA-4) as diamine compound and 70 mol parts of compound (DB-13) as diamine compound were dissolved in NMP, and the reaction was carried out at room temperature for 6 hours to obtain a solution containing 15% by mass of polyamic acid. Next, NMP was added to the obtained polyamic acid solution to obtain a solution with a polyamic acid concentration of 10% by mass, and pyridine and acetic anhydride were added to perform a dehydration ring-closing reaction at 60° C. for 4 hours. After the dehydration ring-closing reaction, the solvent in the system was replaced with fresh NMP to obtain a solution containing 15% by mass of polyimide with an imidization rate of about 80% (this is referred to as polymer (PI-1)).

[0091] [Synthesis examples 18B, 19B] Polyimides (polymers (PI-2) and (PI-3)) were obtained in the same manner as in Synthesis Example 17B, except that the types and amounts of the tetracarboxylic dianhydride and diamine compound used were changed as shown in Table 4.

[0092] [Table 4]

[0093] <Preparation and Evaluation of Liquid Crystal Alignment Agent> [Evaluation Example 2-1: Evaluation of storage stability and transmittance] 1. Preparation of Liquid Crystal Alignment Agent The solution of the polymer (PA-7) obtained in Synthesis Example 7B was diluted with NMP and butyl cellosolve (BC) to obtain a solution with a solvent composition of NMP / BC=80 / 20 (mass ratio) and a solid content concentration of 3.5 mass%. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-1).

[0094] 2. Evaluation of storage stability The liquid crystal alignment agent (AL-1) prepared in 1 above was filtered through a 1.0 μm filter and then stored at room temperature for one month, after which the presence or absence of precipitates in the liquid crystal alignment agent was observed. When no precipitates were observed in the liquid crystal alignment agent, it was rated as "good (○)", and when precipitates were observed, it was rated as "poor (×)". As a result, the storage stability of this example was rated as "good (○)".

[0095] 3.Evaluation of transmittance The liquid crystal alignment agent (AL-1) prepared in 1 above was applied onto a glass substrate using a spinner and heated (pre-baked) on a hot plate at 110°C for 3 minutes. After that, it was dried (post-baked) for 30 minutes in an oven at 230°C with the inside of the oven replaced with nitrogen, forming a coating film with an average thickness of 0.08 μm. The light transmittance (%) of the obtained coating film at a wavelength of 400 nm was evaluated using a spectrophotometer (Hitachi, Ltd., 150-20 type double beam). The evaluation was as follows: if the light transmittance was 97% or more, it was "good (○)", if it was 95% or more and less than 97%, it was "fair (△)", and if it was less than 95%, it was "poor (×)". As a result, the light transmittance of this coating film was 99.0%, and the transmittance was "good".

[0096] [Evaluation Examples 2-2 to 2-6, Comparative Evaluation Examples 2-1 to 2-6, and Reference Evaluation Example 2-1] A liquid crystal alignment agent was prepared in the same manner as in Evaluation Example 2-1, except that the composition of the liquid crystal alignment agent was changed as shown in Table 5. In addition, the storage stability and transmittance of the obtained liquid crystal alignment agent were evaluated. The results are shown in Table 5.

[0097] [Table 5]

[0098] As shown in Table 5, the liquid crystal aligning agents containing the polymer [P] (Evaluation Examples 2-1 to 2-6) had better results in at least one of the storage stability and the transmittance than the liquid crystal aligning agents of Comparative Evaluation Examples 2-1 to 2-6.

[0099] Here, the polymer (PA-2) contained in the liquid crystal alignment agent of Comparative Evaluation Example 2-2 is a polymer obtained by using a diamine (DA-3) having a benzimidazole skeleton. As shown in Table 5, the evaluation of the storage stability and transmittance of the liquid crystal alignment agent containing the polymer (PA-2) was "x". In addition, the polymers (PA-3) and (PI-1) contained in the liquid crystal alignment agents of Comparative Evaluation Examples 2-3 and 2-6 are polymers obtained by using a diamine (DA-4) having a structure in which an amide group and a protected amino group are bonded to an aminophenyl group, and the polymer (PA-4) contained in the liquid crystal alignment agent of Comparative Evaluation Example 2-4 is a polymer obtained by using a diamine (DA-5) having a structure in which a benzene ring having a protected amino group is bonded to an aminophenyl group via an amide bond. As shown in Table 5, the evaluation of the transmittance of the film of the liquid crystal alignment agents containing the polymers (PA-3), (PI-1), and (PA-4) was "x".

[0100] [Example 1: Rubbed FFS type liquid crystal display element] 1. Fabrication of FFS-type liquid crystal display elements using the rubbing method A glass substrate (first substrate) having a flat electrode (bottom electrode), an insulating layer, and a comb-shaped electrode (top electrode) laminated in this order on one side thereof, and a glass substrate (second substrate) having no electrode were prepared. Next, a liquid crystal alignment agent (AL-1) was applied to the electrode-formed surface of the first substrate and one side of the second substrate, respectively, using a spinner, and heated (pre-baked) on a hot plate at 110°C for 3 minutes. Then, the substrate was dried (post-baked) for 30 minutes in an oven at 230°C, the inside of which was replaced with nitrogen, to form a coating film having an average thickness of 0.08 μm. Next, the coating film surface was subjected to rubbing treatment using a rubbing machine having a roll wrapped with rayon cloth, with a roll rotation speed of 1000 rpm, a stage movement speed of 3 cm / sec, and a pile indentation length of 0.3 mm. Then, ultrasonic cleaning was performed in ultrapure water for 1 minute, and then drying was performed in a clean oven at 100°C for 10 minutes to obtain a pair of substrates having a liquid crystal alignment film. Next, a pair of substrates having a liquid crystal alignment film was screen-printed with an epoxy resin adhesive containing aluminum oxide spheres having a diameter of 3.5 μm, leaving a liquid crystal injection port at the edge of the surface on which the liquid crystal alignment film was formed. The substrates were then superimposed and pressed together, and the adhesive was thermally cured at 150°C for 1 hour. Next, a negative liquid crystal (MLC-6608, manufactured by Merck) was filled into the gap between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was then sealed with an epoxy adhesive. Furthermore, in order to remove the flow orientation during liquid crystal injection, the substrate was heated at 120°C and then slowly cooled to room temperature to produce a liquid crystal cell. Note that when the pair of substrates were superimposed, the rubbing methods of the respective substrates were set to be antiparallel. Next, polarizing plates were attached to both outer surfaces of the substrates in the liquid crystal cell to obtain an FFS-type liquid crystal display element.

[0101] 2. Initial VHR assessment The liquid crystal display element manufactured in 1 above was placed in an oven at 60°C, and then the voltage holding ratio (VHR) was measured under the conditions of 1V and 1670msec using a VHR measuring device "VHR-1" manufactured by Toyo Technica Corporation. The evaluation criteria were "good (○)" when the VHR was higher than 73%, "fair (△)" when it was 73% or less and 60% or more, and "poor (×)" when it was less than 60%. As a result, the initial VHR of this example was evaluated as "good (○)".

[0102] 3. Evaluation of VHR reliability The reliability of the voltage holding ratio was evaluated for the liquid crystal display element manufactured in 1 above. The evaluation was performed as follows. First, a voltage of 1V was applied to the liquid crystal display element for 60 microseconds, and then the voltage holding ratio (VHR1) was measured 1670 milliseconds after the application was removed. Next, the liquid crystal display element was irradiated with CCFL (backlight) at 60°C for one week, and then left to stand at room temperature and allowed to cool naturally to room temperature. After cooling, a voltage of 1V was applied to the liquid crystal display element for 60 microseconds, and then the voltage holding ratio (VHR2) was measured 1670 milliseconds after the application was removed. The measurement device used was a VHR measurement device "VHR-1" manufactured by Toyo Corporation. The rate of change in VHR (ΔVHR) at this time was calculated from the difference between VHR1 and VHR2 (ΔVHR=VHR1-VHR2), and the VHR reliability was evaluated based on ΔVHR. If ΔVHR was less than 15%, it was judged as "good (○)", if it was between 15% and 20%, it was judged as "fair (△)", and if it was more than 20%, it was judged as "poor (×)". As a result, the VHR reliability in this example was "good (○)".

[0103] 4. Evaluation of liquid crystal alignment after keystroke test 1 (evaluation by number of bright spots) The liquid crystal display element manufactured in 1 above was evaluated for its liquid crystal alignment after a keystroke test. The evaluation was performed as follows. A silicone rubber pen 3R (manufactured by Touch Panel Laboratory Co., Ltd.) with a tip shape of 3 mm radius was set on the keystroke section (solenoid type) of a keystroke tester (Touch Panel Laboratory Co., Ltd.), and the pen tip was set so that it was at the center position of the liquid crystal display element. After 10,000 keystrokes were performed with the silicone rubber pen at a load of 500 g and 10 Hz, the liquid crystal display element was observed under a microscope (100 times) to evaluate the liquid crystal alignment after the keystroke test. When the number of bright spots was less than 30, it was judged as "excellent (◎)", when it was 30 or more and less than 50, it was judged as "good (○)", when it was 50 or more and less than 100, it was judged as "fair (△)", and when it was 100 or more, it was judged as "poor (×)". As a result, in this example, it was rated as "good (○)".

[0104] 5. Evaluation of liquid crystal alignment after keystroke test 2 (evaluation by retardation change rate) The LCD element used in 4 above was 27,000cd / m 2 The liquid crystal alignment was evaluated by the retardation change rate before and after backlight irradiation. First, the retardation of the liquid crystal display element used in 4 above was measured using Axoscan manufactured by Optoscience, and the retardation change rate α before and after backlight irradiation was calculated using the following formula (z-1). The smaller the change rate α, the better the liquid crystal alignment. A change rate α of 1% or less was evaluated as "good (○)", a change rate α of more than 1% and less than 2% was evaluated as "fair (△)", and a change rate α of more than 2% was evaluated as "poor (×)". α=Δθ / θ1 …(z-1) (In formula (z-1), Δθ represents the retardation difference before and after irradiation, and θ1 represents the retardation value before irradiation.) As a result, this example was rated as "good (◯)".

[0105] [Examples 2 to 10 and Comparative Examples 1 to 7] A liquid crystal alignment agent was prepared in the same manner as in Example 1, except that the composition of the liquid crystal alignment agent was changed as shown in Table 6. In addition, an FFS-type liquid crystal display element was manufactured by a rubbing method in the same manner as in Example 1 using the obtained liquid crystal alignment agent, and the initial VHR, VHR reliability, keystroke test, and alignment after the keystroke test were evaluated. The results are shown in Table 6. In Examples 2, 4, 5, 7, and 9, and Comparative Examples 3 and 4, two types of polymers were used as the polymer component, and in Examples 6 and 10, three types of polymers were used as the polymer component. In Table 6, the numerical value in the polymer column indicates the blending ratio (parts by mass) of the solid content of each polymer relative to 100 parts by mass of the total amount of the polymer components used in the preparation of the liquid crystal alignment agent.

[0106] [Table 6]

[0107] As shown in Table 6, Examples 1 to 10, which used a liquid crystal alignment agent containing the polymer [P], showed better results in terms of initial VHR, VHR reliability, and liquid crystal alignment after the typing test than Comparative Examples 1 to 7, which used a liquid crystal alignment agent not containing the polymer [P].

[0108] It is considered that the liquid crystal anchoring force of the liquid crystal alignment film is largely influenced by the uniaxiality of the film. In this respect, the liquid crystal alignment film formed using the polymer [P] having the partial structure (A) has high uniaxiality, and the liquid crystal alignment after the keystroke test is considered to be good. In contrast, the polymers (PA-3), (PA-4), and (PI-1), which are considered to form a benzimidazole ring structure by intramolecular cyclization reaction like the polymer [P], are considered to form a mesogenic skeleton containing an imide ring structure and a benzimidazole ring structure when the benzimidazole ring structure is formed by post-baking. When the mesogenic skeleton contains a benzimidazole ring structure, the uniaxiality of the film is lower than that of the polymer [P] used in Examples 1 to 10, and the liquid crystal alignment after the keystroke test is considered to be insufficient.

[0109] [Example 11: Optical FFS type liquid crystal display element] 1. Preparation of Liquid Crystal Alignment Agent A solution containing 60 parts by mass of the polymer (PA-7) obtained in Synthesis Example 7B and a solution containing 40 parts by mass of the polymer (PA-11) obtained in Synthesis Example 11B were mixed and diluted with NMP and BC to obtain a solution with a solvent composition of NMP / BC=80 / 20 (mass ratio) and a solid content concentration of 3.5% by mass. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-11).

[0110] 2. Fabrication of FFS-type LCD elements using the photoalignment method A first substrate and a second substrate were prepared similarly to those in Example 1. Next, a liquid crystal alignment agent (AL-11) was applied to the electrode-forming surface of the first substrate and one of the substrate surfaces of the second substrate using a spinner, and heated (pre-baked) on a hot plate at 80°C for 1 minute. Thereafter, the substrate was dried (post-baked) for 30 minutes in an oven at 230°C with the interior replaced with nitrogen, forming a coating film with an average thickness of 0.1 μm. The obtained coating film was irradiated with 1,000 J / m2 of linearly polarized ultraviolet light including a 254 nm emission line using an Hg-Xe lamp. 2 The coating film was irradiated with light from the normal direction of the substrate to perform a photo-alignment treatment. The amount of irradiation was measured using an actinometer that measures at a wavelength of 254 nm. Next, the coating film that had been subjected to the photo-alignment treatment was heated in a clean oven at 230°C for 30 minutes to perform a heat treatment, thereby forming a liquid crystal alignment film. Next, for one of the pair of substrates on which the liquid crystal alignment film was formed, an epoxy resin adhesive containing aluminum oxide spheres with a diameter of 3.5 μm was applied by screen printing to the outer edge of the surface having the liquid crystal alignment film. Then, the substrates were overlapped and pressed together so that the projection direction of the polarization axis on the substrate surface during light irradiation was antiparallel, and the adhesive was thermally cured at 150°C for 1 hour. Next, negative liquid crystal (MLC-6608, manufactured by Merck) was filled between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive to obtain a liquid crystal cell. Furthermore, in order to remove the flow alignment during liquid crystal injection, the liquid crystal cell was heated at 120°C and then slowly cooled to room temperature. Then, polarizing plates were attached to both outer surfaces of the substrate in the liquid crystal cell to obtain a liquid crystal display element. In addition, the above series of operations was performed with a UV irradiation dose of 100 to 10,000 J / m after post-baking. 2 By varying the exposure dose within the range of 100%, three or more liquid crystal display elements with different UV exposure doses were manufactured, and the liquid crystal display element with the exposure dose (optimum exposure dose) that showed the best alignment characteristics was used for the following evaluation of initial VHR and VHR reliability.

[0111] 3. Evaluation For the liquid crystal display element manufactured in the above 2, the initial VHR, VHR reliability, and liquid crystal alignment after a keystroke test were evaluated in the same manner as in Example 1.

[0112] [Examples 12 to 14 and Comparative Example 8] A liquid crystal alignment agent was prepared in the same manner as in Example 11, except that the composition of the liquid crystal alignment agent was changed as shown in Table 7. In addition, using the obtained liquid crystal alignment agent, an FFS-type liquid crystal display element was manufactured by a photoalignment method in the same manner as in Example 11, and various evaluations were performed. The results are shown in Table 7. In Table 7, the numerical values ​​in the polymer column indicate the blending ratio (parts by mass) of the solid content of each polymer relative to 100 parts by mass of the total amount of the polymer components used in the preparation of the liquid crystal alignment agent.

[0113] [Table 7]

[0114] As shown in Table 7, Examples 11 to 14, which used a liquid crystal alignment agent containing polymer [P], showed better results in initial VHR, VHR reliability, and liquid crystal alignment after keystroke test than Comparative Example 8, which used a liquid crystal alignment agent not containing polymer [P].

[0115] From the above results, it was revealed that the liquid crystal alignment agent containing the polymer [P] having the partial structure (A) can form a liquid crystal alignment film with high transmittance, and can produce a liquid crystal element with little decrease in voltage retention rate (i.e. high reliability) even when used for a long period of time and excellent touch panel resistance. In addition, the liquid crystal alignment agent containing the polymer [P] also had good storage stability.

Claims

1. A liquid crystal aligning agent comprising a polymer [P] having, in its main chain, at least one partial structure (A) selected from the group consisting of a partial structure represented by the following formula (1-1) and a partial structure represented by the following formula (1-2): 【Chemistry 1】 (In formula (1-1) and formula (1-2), R 1 and R 4 R is each independently a monovalent thermally detachable group. 2 , R 3 , R 5 and R 6 R is each independently a hydrogen atom or a monovalent organic group. 7 and R 8 are each independently a halogen atom or an alkyl group having 1 to 5 carbon atoms. n1 and n2 are each independently an integer of 0 to 3. When n1 is 2 or 3, multiple R7s in the formula are the same or different. When n2 is 2 or 3, multiple R 8 are the same or different. 1 , -O-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO- or * 1 -CO-NR 9 -. R9 is a hydrogen atom or a monovalent organic group. 1 " represents a bond to the benzene ring in the formula. 1 is an alkanediyl group having 1 to 10 carbon atoms. "*" represents a bond.

2. The liquid crystal aligning agent according to claim 1 , wherein the polymer [P] contains a structural unit derived from a diamine having the partial structure (A).

3. The diamine is at least one selected from the group consisting of compounds represented by the following formula (2-1) and compounds represented by the following formula (2-2): 【Chemistry 2】 (In formula (2-1) and formula (2-2), Y 1 , Y 2 , Y 3 and Y 4 are each independently a divalent organic group. 1 and B 2 are each independently a single bond or an alkanediyl group having 1 to 10 carbon atoms. 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , n1, n2, X 1 and A 1 has the same meaning as the above formula (1-1) and formula (1-2).

4. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein the polymer [P] is at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.

5. The liquid crystal aligning agent according to any one of claims 1 to 4, wherein the polymer [P] has a structural unit derived from an alicyclic tetracarboxylic dianhydride.

6. The liquid crystal aligning agent according to any one of claims 1 to 5, further comprising a polymer [Q] that does not have the partial structure (A).

7. A liquid crystal alignment film formed by the liquid crystal aligning agent according to any one of claims 1 to 6.

8. A step of forming a coating film using the liquid crystal aligning agent according to any one of claims 1 to 6; a step of subjecting the coating film to a light irradiation treatment to impart liquid crystal alignment ability; A method for producing a liquid crystal alignment film comprising the steps of:

9. A liquid crystal element comprising the liquid crystal alignment film according to claim 7 .

10. A polyamic acid, a polyamic acid ester, and a polyimide each having a structural unit derived from at least one selected from the group consisting of a compound represented by the following formula (2-1) and a compound represented by the following formula (2-2): 【Chemistry 3】 (In formula (2-1) and formula (2-2), R 1 and R 4 R is each independently a monovalent thermally detachable group. 2 , R 3 , R 5 and R 6 R is each independently a hydrogen atom or a monovalent organic group. 7 and R 8 are each independently a halogen atom or an alkyl group having 1 to 5 carbon atoms. n1 and n2 are each independently an integer of 0 to 3. When n1 is 2 or 3, multiple R 7 When n2 is 2 or 3, multiple R 8 are the same or different. 1 , -O-, * 1 -CO-O-, * 1 -O-CO-, -NR 9 -, * 1 -NR 9 -CO- or * 1 -CO-NR 9 -. R9 is a hydrogen atom or a monovalent organic group. 1 " represents a bond to the benzene ring in the formula. 1 is an alkanediyl group having 1 to 10 carbon atoms. 1 , Y 2 , Y 3 and Y 4 are each independently a divalent organic group. 1 and B 2 are each independently a single bond or an alkanediyl group having 1 to 10 carbon atoms.

Citation Information

Patent Citations

  • Liquid crystal aligning agent, liquid crystal alignment layer, and liquid crystal display element

    JP2010054872A

  • Liquid crystal alignment treatment agent, liquid crystal alignment film, and liquid crystal display element equipped with the liquid crystal alignment film

    WO2012002501A1

  • Novel diamine, polymer, liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element using same

    WO2014104015A1